Pengelolaan Kelompok Bermain dan Taman Kanak-kanak Aisyiyah 21 Muhammadiyah Rawamangun, Jakarta Timur - Yusria, Yusria (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
This writing describes about mqnqgement of the playgroup and the kindergarten of Aisyiyah Muhammadiyah Cabang Rawamangun Jakarta Timur. They are ones of nonformal education which purposes to help the growth and development of potential child both physically and mental spiritual, so child ready to take advance of education, as written at laws of national education system 2003.